2022
DOI: 10.29294/ijase.8.3.2022.2235-2241
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Thermal Profile of a Crop Dryer Powered by Generator Exhaust Gas Waste Heat

Abstract: The thermal profile of an exhaust gas waste heat recovery (WHR) crop dryer is presented. The dryer uses a parallel flow heat exchanger to recover the exhaust gas waste heat of a diesel engine generator for the drying of food crops. No-load tests of the assembled test rig were conducted to study the temperature profile and heat transfer rates in the dryer at varying inlet ambient air velocities. The results of the no-load tests revealed that the higher the airspeed through the WHR heat exchanger, the faster the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Ternyata penurunan kelembaban relatif lebih efektif menurunkan kadar air dari pada peningkatan suhu dimana model Page yang paling sesuai dengan R 2 = 0,98-0,99 untuk variasi kelembaban, sedangkan R 2 = 0,98 untuk variasi suhu [6]. Menginvestigasi model matematik kinetika pengeringan rumput laut Kappaphycus akibat perubahan suhu (30,40,50, dan 60 C), kelembaban (20, 30 dan 40% RH) pada kecepatan udara 1 m s -1 dijaga konstan menggunakan pengering konvektif. Kinetika pengeringan menurut model Newton, Page, Henderson & Pabis.…”
Section: Pendahuluanunclassified
“…Ternyata penurunan kelembaban relatif lebih efektif menurunkan kadar air dari pada peningkatan suhu dimana model Page yang paling sesuai dengan R 2 = 0,98-0,99 untuk variasi kelembaban, sedangkan R 2 = 0,98 untuk variasi suhu [6]. Menginvestigasi model matematik kinetika pengeringan rumput laut Kappaphycus akibat perubahan suhu (30,40,50, dan 60 C), kelembaban (20, 30 dan 40% RH) pada kecepatan udara 1 m s -1 dijaga konstan menggunakan pengering konvektif. Kinetika pengeringan menurut model Newton, Page, Henderson & Pabis.…”
Section: Pendahuluanunclassified
“…This reduces the capacity of the exhaust gas to appreciably heat the drying air. However, this problem was solved by replacing the turbine-dynamo arrangement with a solar panel as the source of electricity for the dryer, thereby utilizing the energy content of the exhaust gas only for heating the drying air, which improved the heating rate of the drying chamber significantly [ 125 ]. The dryer was successfully used to dry maize grains and sliced yam samples [ [126] , [127] , [128] ].…”
Section: Opportunities For Waste Heat Recovery In the Food Processing...mentioning
confidence: 99%
“…𝑐 𝑝 = 962.097 + 0.1507𝑇 𝑔 --( 13) 𝐾 𝐶𝑁 = 8.459 × 10 −3 + 5.7 × 10 −5 𝑇 𝑔 --( 14) 𝜇 = 1.384 × 10 −5 + 2.68 × 10 −8 𝑇 𝑔 -- (15) where 𝜌 is the density; 𝑐 𝑝 , the heat capacity; 𝐾 𝐶𝑁 , the thermal conductivity; 𝜇, the dynamic viscosity, and 𝑇 𝑔 , the temperature, of the exhaust gas.…”
Section: Working Fluid Modelmentioning
confidence: 99%
“…These heat losses through the exhaust gas could go up to 40% [12,13], which is a huge waste. However, to ensure a substantial reduction of fossil fuel consumption in order to minimize its negative impact on the environment, manufacturers now place priority on either renewable energy facilities or try to reduce energy waste in IC engines, using waste heat recovery (WHR) techniques [14,15]. Reshid et al, [16] observed that a significant amount of heat can be recovered from the exhaust gas of an IC engine to take care of other thermal needs, thus improving energy efficiency in the range of 30 -50%.…”
Section: Introductionmentioning
confidence: 99%